Analyzing the Effect of Information Credibility towards Brand Trust in Green Marketing - Ridwan Andi Purnomo, Muhammad; Bin Hassan, Azmi; Pasca Hendradewa, Andrie; Santika, Wina (International Journal of Psychosocial Rehabilitation, 2020)
Marketing is the process of planning and executing the conception, pricing, promotion, and distribution of ideas, goods, and services to create exchanges that satisfy individual (customer) and organizational objectives. Green marketing has recently become an interesting issue; it is divided into green marketing strategy and marketing mix. The marketing mix is divided into 4 categories, which are product, price, place, and promotion. Promotion is needed to communicate products or services to customers; information credibility is needed to deliver information properly. The aim of the research is to identify the relationship among variables. Those variables are familiar brand, credible source, initial perception, and website interactivity as exogenous variables, while brand trust is an endogenous variable. Another purpose is designing a conceptual model of information credibility toward brand trust in green marketing scope. The research was conducted using the SEM (Structural Equation Model) method, processed by AMOS 22 software. There are several steps to the research: measurement models, structural models, and modification models. The results show there are two variables that significantly influence purchasing decisions, namely familiar brand and website interactivity.